PRAKTIK KEPEMIMPINAN ISLAM (STUDI FENOMENOLOGI PADA MANAJER RUMAH SAKIT PKU MUHAMMADIYAH TEMANGGUNG) - Widya Hapsari, Gusti; Mas’ud, Fuad (Diponegoro Journal of Management, 2018)
Basically, in Islamic perspective every human being is a leader whether for himself or another. Leadership someday will be counted in the presence of Allah SWT. Therefore, an Islamic leader is prohibited to act according to his will and his group but must follow the rules derived from Al-quran and As-sunnah. The main purpose of this research is to analyze and discuss the implementation of Islamic values in leadership functions. The method used in this research  is qualitative and phenomenology study approach. The method is choosen in order to archive  the participant’s life experience related to the phenomenon of Islamic leadership in RS PKU Muhammadiyah Temanggung. In attempt to collect the data, this research uses interview, observation, and documentation within a certain period of time. The finding of this research shows that managers of RS PKU Muhammadiyah Temanggung apply Islamic values such as siddiq (truthful), amanah (trustworthy), tabligh (deliver), and fatanah (smart) in instructive, consultative, control, and exemplary leadership functions.